Prevalence Of Diabetes Mellitus in Urban Population of Ahmadabad City, Gujarat - Koria, Bharti; Kumar, Rupesh; Nayak, Ashish; Kedia, Geeta (National Journal of Community Medicine, 2013)
Background: India leads the world with largest number of diabetic subjects earning the dubious distinction of being termed the “diabetes capital of the world”. The number of people with diabetes in India currently around 40.9 million is expected to rise to 69.9 million by 2025 unless urgent preventive steps are taken. Rapid epidemiological transition associated with higher prevalence of diabetes in the urban population. Objectives: To find out prevalence of diabetes mellitus among urban population of Ahmedabad city. Materials and Methods: A community based cross sectional study was conducted in Ahmedabad city by house to house survey. Results: Prevalence of diabetes in Ahmedabad City is 7.33%. Majority of the study population (53.64%) was between 45-60 years. Among diabetic population 37.37% housewives and 16.36% were having government job. Conclusions: There is a large heterogeneity of diabetes prevalence within urban populations in India. There are few community based studies done in Ahmedabad city for prevalence of diabetes. It is important to have region-specific prevalence data of diabetes so that appropriate.